2018
DOI: 10.3389/fncel.2018.00271
|View full text |Cite
|
Sign up to set email alerts
|

The Endocannabinoid/Cannabinoid Receptor 2 System Protects Against Cisplatin-Induced Hearing Loss

Abstract: Previous studies have demonstrated the presence of cannabinoid 2 receptor (CB2R) in the rat cochlea which was induced by cisplatin. In an organ of Corti-derived cell culture model, it was also shown that an agonist of the CB2R protected these cells against cisplatin-induced apoptosis. In the current study, we determined the distribution of CB2R in the mouse and rat cochleae and examined whether these receptors provide protection against cisplatin-induced hearing loss. In a knock-in mouse model expressing the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
74
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(79 citation statements)
references
References 61 publications
5
74
0
Order By: Relevance
“…The underlying mode of action of Cnr2 in any of those cells/tissue remains to be determined. However, both groups demonstrated that Cnr2 expression was up-regulated after Cisplatin exposure [11,12]. This was strengthening an earlier claim for an anti-apoptotic role for Cnr2 in cisplatin-treated cultured cells of an auditory cells line [76].…”
Section: Cnr2 Expression In Physiologically Active and Mature Hcs Ofsupporting
confidence: 79%
See 3 more Smart Citations
“…The underlying mode of action of Cnr2 in any of those cells/tissue remains to be determined. However, both groups demonstrated that Cnr2 expression was up-regulated after Cisplatin exposure [11,12]. This was strengthening an earlier claim for an anti-apoptotic role for Cnr2 in cisplatin-treated cultured cells of an auditory cells line [76].…”
Section: Cnr2 Expression In Physiologically Active and Mature Hcs Ofsupporting
confidence: 79%
“…Strong immunolabelling of Cnr2 was found in the stria vascularis (SV), and maybe more surprisingly in all inner HCs (IHCs), as well as in the afferent neurites and cell bodies of spiral neurons [11]. All these localizations were confirmed independently, and additional cochlear expression was found in the spiral ligament (SL), the outer HCs (OHCs) and a subset of support cells (SCs), namely the inner and outer pillar cells (IPCs and OPCs respectively) [12]. Furthermore, this group showed that Cnr2 was co-localizing with markers of fibroblasts in the SL, basal cells in the SV, and ribbon synapse (Ribeye B or CtBP2) in the IHCs [12].…”
Section: Cnr2 Expression In Physiologically Active and Mature Hcs Ofmentioning
confidence: 88%
See 2 more Smart Citations
“…This effect was found to be mediated in part by inhibition of STAT1, thereby preventing cell death in the cochlea. 43 An extract from green tea epigallocatechin-3gallate (EGCG) was shown to protect against cisplatin ototoxicity in the rat and tumor-bearing mouse without interference with the tumor killing efficacy of cisplatin. 15 EGCG protected against cisplatin-induced hair cell damage, ABR threshold shifts, and prevented a decrease in the strial Na/K-ATPase activity.…”
Section: Protective Agents-preclinical Studiesmentioning
confidence: 99%